Lessons from the Polder: Is Dutch CO2-Taxation Optimal? - Herman Vollebergh (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper evaluates energy tax reform in the Netherlands between 1988 and 2002 from a climate change perspective. A tax on fuels and the so-called regulatory energy tax since 1996 are examples of indirect and non-uniform taxation of emissions. The overall tax base and rate structure corroborates recent theoretical findings that heterogeneity in production processes and transaction costs may justify optimal departures from the Pigovian corrective tax rule. Surprisingly, the Dutch revenue-raising tax matches the (modified) Pigovian policy prescription rather well, whereas the regulatory energy tax mainly follows the revenue raising Ramsey logic. Further improvements of the energy tax structure are also discussed, such as targeting the energy tax base and linking the tax rate more precisely to fuel characteristics.
Keywords: H30; Q48; 330; Climate change; Energy taxes; Optimal indirect taxation; Specific and ad valorem taxation; Energiesteuer; Ökosteuer; Optimale Besteuerung; Klimawandel; Niederlande